2014
DOI: 10.1039/c3cp53495b
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical dynamics of E-methylfurylfulgide—kinematic effects on photorelaxation dynamics of furylfulgides

Abstract: With the present theoretical study of the photochemical switching of E-methylfurylfulgide we contribute an important step towards the understanding of the photochemical processes in furylfulgide-related molecules. We have carried out large-scale, full-dimensional direct semiempirical configuration-interaction surface-hopping dynamics of the photoinduced ring-closure reaction. Simulated static and dynamical UV/Vis-spectra show good agreement with experimental data of the same molecule. By a careful investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
3
27
1
Order By: Relevance
“…The scenario is further supported by recent state-averaged CASSCF/CASPT2 calculations for photo-excited Z-MeF, where converged S 1 -S 0 CI structures could be obtained. 24 The distinctive feature of the CI structures is a twist along the C 4 QC 5 double bond corresponding to a dihedral angle of 901 in line with the scenario suggested above. The proposed direct photoisomerisation of Z-fulgides differs from the accepted model for the E -Z photoisomerisation of unpolar polyenes including This is © the Owner Societies 2014 hexatriene (HT) via an optically dark intermediate state, [36][37][38][39][40][41][42][43][44][45] but is in line with the suggested situation for biomimetic dipolar NAIP photoswitches, where the photo-excited state is zwitterionic.…”
Section: Photoisomerisation Pathwayssupporting
confidence: 71%
See 2 more Smart Citations
“…The scenario is further supported by recent state-averaged CASSCF/CASPT2 calculations for photo-excited Z-MeF, where converged S 1 -S 0 CI structures could be obtained. 24 The distinctive feature of the CI structures is a twist along the C 4 QC 5 double bond corresponding to a dihedral angle of 901 in line with the scenario suggested above. The proposed direct photoisomerisation of Z-fulgides differs from the accepted model for the E -Z photoisomerisation of unpolar polyenes including This is © the Owner Societies 2014 hexatriene (HT) via an optically dark intermediate state, [36][37][38][39][40][41][42][43][44][45] but is in line with the suggested situation for biomimetic dipolar NAIP photoswitches, where the photo-excited state is zwitterionic.…”
Section: Photoisomerisation Pathwayssupporting
confidence: 71%
“…Previous experimental and theoretical studies the selected fulgide derivatives were able to relate the observed significant changes in the photoswitching behaviour of the respective E-and C-isomers to details of the ultrafast photo-induced dynamics affected by steric constraints at the central HT unit, intramolecular bridging, or by extension of the p-electron system of the furyl unit. 10,16,[19][20][21][22][23][24] However, the only apparent effect of the structural modifications for the photo-excited Z-fulgides is a moderate slowing of the excited-state dynamics, with time constants ranging from t 1 = 0.18 ps for Z-MeF to t 1 = 0.32 ps for Z-MeBF. The very similar results for all four photo-excited Z-isomers indicate that the underlying Z -E photoisomerisation mechanism remains unaltered by the structural changes.…”
Section: Effects Of Structural Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final evaluations are done for 967, 1013, 1045, and 856 trajectories of SPc, SPt, SPmc, and SPmt that are finished successfully in the photodynamics runs. Further technical details are given in previous publications. …”
Section: Computational Detailsmentioning
confidence: 99%
“…85 Further technical details are given in previous publications. [86][87][88][89][90][91][92][93][94][95]…”
Section: Computational Detailsmentioning
confidence: 99%